(untitled) (International conference on multidisciplinary science, 2024)
Currently, long-acting suture materials are used in surgery, which allow tissues to grow together differentially , taking into account the peculiarities of their structure and renewal periods. The emergence of new suture materials in modern surgery creates new technological requirements for the study of atraumatic surgical needles: this is a decrease in the diameter of the punctured channel, resistance, quality of fixation of the thread in the eye of the needle, etc.